An Assessment For A New Approach To Pulsating Lubrication Strategy (PLS) In End Milling - Kasim, Mohd Shahir; Mohd Shahrim, Mohammad Shah All Hafiz; Raja Abdullah, Raja Izamshah; W. Mohamad, W Noor Fatihah; Abdullah, Abu; Jaafar, Mohd Fairuz (Springer, 2019)
This paper presents the result of pulsating lubrication strategy (PLS), an alternative metalworking fluids approach to improve machining performance. The formation of built-up edge (BUE) and built-up layer (BUL) is among the problems encountered during the machining of aluminum alloy, which degrades cutting performance and thus affects the machined surface quality. This study focuses on chip removal effectiveness by jetting a coolant intermittently of PLS on the cutting tool to create a hydraulic shock. The water stream coolant was set to pulsate at 2000 pulse/min with the pressure of 0.76 MPa. Applying this method improves chip evacuation. Hence, minimizing the formation of BUE and BUL more effectively than dry cutting.